LANGUAGE DEVELOPMENT OF EARLY CHILDREN THROUGH STORYTELLING METHODS IN NU 01 YOSOWILANGUN MUSLIMAT KINDERGARTEN - Cholis, Wahyuniati; Fadil , Djamali; Riza , Wahyu Utami (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2023)
Language development (linguistics) is a child’s development in acquiring words effectively, both spoken and written. Children’s language development from an early age through the story telling method applied at the Muslimat NU 01 Yosowilangun kindegarteen aim to broaden horizon and knowledge as well as as communication tool and help children to interact well wih their sosial environment. The story telling method is an effort to develop language skills in early childhood. So the reasercher raised the problem of how children ‘s language development occour aften an early age through the story telling method at Muslimat NU 01 Yosowilangun Kindegarteen. To answer the research problem, a qualitative descriptive type of research was used. The research subject were teacher and student. The data collection technique were observation, interview, and docomentation. The result of reaserch are the development of story telling methode has been developed for children language development from an early age. In implementation the teacher has optimally used the story telling methode. Qualitative data analysis is inductive in nature namely an analysis based on the data obtained, then developed. The data revealed that out of 10 children, 3 children (20%), were included in the BSB (according to expextation) category, 1 children (6%) was included in the MB (developing) category, and no one children in the BB (not yet developing) showing that 94% of children’s language skills are in very good categoryand developing as expected